PERBANDINGAN KONTRAK LUMP SUM DAN UNIT PRICE PADA PELAKSANAAN PEKERJAAN PAGAR (Studi Kasus: Proyek PT. United Tractors Tbk – Jakarta) - Ma'sun, Arif Muhammad; -, Mirnayani (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
In construction projects, contract types play a crucial role in determining project success. This study examines the implementation of Lump Sum and Unit Price contracts in a fence construction project undertaken by PT. United Tractors Tbk in Jakarta. The research identifies the challenges and discrepancies arising from the use of Lump Sum contracts, especially when complete documentation is not available during the bidding process. A descriptive quantitative method is employed to analyze field data, interviews, and surveys with relevant stakeholders. The findings indicate that the Lump Sum contract led to significant additional work claims amounting to 16% of the initial contract value due to incomplete initial documentation and design changes during execution. The study also compares the Lump Sum contract with a hypothetical Unit Price contract scenario, revealing a potential cost deviation of 22.19%. The evaluation suggests that the Lump Sum contract was less suitable for this project, recommending the Unit Price contract as a more flexible alternative to accommodate changes and uncertainties in construction projects.